The functions and use of Roman coinage : an overview of 21st century scholarship - Kemmers, Fleur (Brill research perspectives. Ancient history., 2019)
In this publication Fleur Kemmers gives an overview of 21st century scholarship on Roman coinage for students and scholars in the fields of ancient history and Roman archaeology. First, it addresses the study of numismatics as a discipline and the theoretical and methodological advances of the last decades. Secondly, it provides guidelines on how to consult numismatic reference works, including those available online. Recent scholarly approaches and insights in the functions of Roman coins as both vehicles of political communication and instruments for state payments are critically assessed. Furthermore, the publication reviews the evidence for a conscious monetary policy on the part of the Roman authorities. Finally, the impact of Roman expansion and imperialism on monetisation and coin use in Rome's Empire is discussed.